NATIONAL - CULTURAL AND PHYSICAL GENOCIDE ON THE MACEDONIANS (1913-2013) (Annual of the Faculty of Philosophy in Skopje, 2015)
In the article, a synthesis is given regarding separated aspects of „the Macedonian question“ in the period of 1913-2013, in which the Macedonians were asimilated, denationalised, etnically distincted, their national uniquist was neglected, as well as their tradition, language, history and culture by their neighbors. Therefore the starting point are the Balkan Wars which brought numerous changes in the destinies of the Maedonians and which are forming a watersplit in the macedonian history. The wars for conquering of Macedonia, continued in the World War I, while the piece agreement in Bukurešt and Versaj offered „final solution “ for the macedonian qestion by dividing of the etno-geographical theritory of Macedonia. The macedonian nation was left to live under the goverments of four independent states, until the World War 2 when in Vardar Macedonia was created Democratic Federal Macedonia, as a part of Federal Yugoslavia. After 1991, with the collapse of the federation it was declared Sovereign Independent Republic of Macedonia. In the article, among other things, are required answers for the following questions: Why the neighbors did not greet the independency? Why the Balkan war was declared (or continued) as special “cold“ war? Why Republic of Macedonia for more than 20 years is waiting outside the doors of EU and NATO? Why those who are creating the European and world politics, in the case of Republic of Macedonia are having double standards and are breaching their own conventions and declarations?
Keywords: GENOCIDE; ASSIMILATION; BALKAN WARS; BUCHAREST AGREEMENT; MACEDONIA